Navigating Recent Changes in Dosing Information: Dynamics of FDA‐Approved Monoclonal Antibodies in Post‐Marketing Realities - Nai Lee; Su‐jin Rhee; Seong Min Koo; So Won Kim; Gyo Eun Lee; Yoon A Yie; Yun Kim (Clinical and Translational Science)
ABSTRACT Monoclonal antibodies (mAbs) are critical components in the therapeutic landscape, but their dosing strategies often evolve post‐approval as new data emerge. This review evaluates post‐marketing label changes in dosing information for FDA‐approved mAbs from January 2015 to September 2024, with a focus on both initial and extended indications. We systematically analyzed dosing modifications, categorizing them into six predefined groups: Dose increases or decreases, inclusion of new patient populations by body weight or age, shifts from body weight‐based dosing to fixed regimens, and adjustments in infusion rates. Among the 86 mAbs evaluated, 21% (n = 18) exhibited changes in dosing information for the initial indication, with a median time to modification of 37.5 months (range: 5–76 months). Furthermore, for mAbs with extended indications (n = 26), 19.2% (n = 5) underwent dosing changes in their first extensions, with a median time to adjustment of 31 months (range: 8–71 months). Key drivers for these adjustments included optimizing therapeutic efficacy, addressing safety concerns, accommodating special populations, and enhancing patient convenience. We also discuss the role of model‐informed drug development, real‐world evidence, and pharmacogenomics in refining mAb dosing strategies. These insights underscore the importance of ongoing monitoring and data integration in the post‐marketing phase, providing a foundation for future precision medicine approaches in mAb therapy.